Formation of Methodological Readiness of Undergraduates of the Psychological and Pedagogical Direction for Mediation in Conditions of Blended Learning - N.A. Ivanov; O.G. Smolyaninova; A.A. Smolyaninov (Moscow State University of Psychology and Education, 2023)
The article presents the problem of conceptualization of the phenomenon of «methodical readiness for mediation» as a special case of professional readiness of a teacher-psychologist to implement mediation in education. The results of a pedagogical experiment on the formation of methodological readiness of undergraduates in conditions of blended learning are described. The main idea of the study is that methodological training is a propaedeutics of professional readiness for mediation in general. The organization of the educational process is based on the principles of practice-oriented and event-based approaches and involves immersion of undergraduates in the basics of mediation in a blended learning environment. The features of the formation of methodological readiness for mediation in conditions of blended learning, based on the principle of humanitarization, ensuring the innovative use of the mediation approach in educational practices, are determined. 92 undergraduates of the Siberian Federal University (SibFU), studying under the programs of the psychological and pedagogical master's degree in 2020-2023, took part in the experimental work. Methodological materials in the field of mediation developed and implemented by SibFU undergraduates during their professional training are presented.